Surgical stress response in dogs diagnosed with pyometra undergoing ovariohysterectomy - Lövebrant, Johanna (SLU/Dept. of Clinical Sciences (until 231231), 2013)
The aim of this study was to investigate the intraoperative surgical stress response in dogs undergoing ovariohysterectomy and to compare acepromazine and medetomidine as premedications. 15 dogs diagnosed with pyometra were used in this study. Blood pressure and heart rate were used as parameters to measure surgical stress response. The surgery was divided into four phases. Phase 0 was the period 10 minutes before the skin incision, phase 1 was skin incision and opening of abdomen, phase 2 was manipulation of uterine horns, ligation and transection of mesovarium and phase 3 was ligation of cervix, removal of organs and closing the abdomen.